Ga and Ge-doped graphene structures: A DFT study of sensor applications for methanol - Geçim, Gözde; Özekmekçi, Mehtap; Fellah, Mehmet Ferdi (Elsevier, 2020)
Density functional theory calculations have been carried out to investigate the adsorption of methanol on the surface of Ga and Ge-doped graphene clusters and in order to explore the potential of doped graphene as a gas sensor. The hybrid B3LYP method with 6-31G (d,p) and LANL2DZ basis sets were used in this study. The charge distributions of structures show that both Ga-doped and Ge-doped graphene structures are sensitive to methanol molecule. The HOMO-LUMO gap of the Ga-doped and Ge-doped graphene structures decreased when methanol adsorbed on these structures. This result indicates that electrical conductivity of both structures have increased. Hence, Ga-doped and Ge-doped graphene structures could be utilized as a gas sensing material in order to detect methanol. Furthermore, the higher electrical conductivity and the smaller recovery time of Ge-doped graphene than those of Ga-doped graphene make it more sensitive and useful in terms of methanol sensing.
FELLAH, Mehmet Ferdi/0000-0001-6314-3365; Gecim, Gozde/0000-0002-2404-8995
Keywords: Graphene; Methanol; Sensor; Adsorption; DFT